PROP taster status, food preferences and consumption of high‐calorie snacks and sweet beverages among 6‐year‐old ethnically diverse children - Wijtzes, Anne I. (Matern Child Nutr, 2016)
A healthy diet is important for optimal growth and development in children. Food preferences are a main determinant of children's intake. The aim of this study was to examine the associations of 6‐n‐propylthiouracil (PROP) taster status (taste sensitivity to PROP) with children's food preferences and consumption of high‐calorie snacks and sweet beverages among ethnically diverse children. We analysed data from 5585 6‐year‐old children enrolled in the Generation R Study, a birth cohort study in Rotterdam, the Netherlands. PROP taster status was evaluated using a suprathreshold screening solution. Food preferences of the children were assessed by a two‐stage protocol using photographs of eight food items (candy, chocolate, mayonnaise, whipped cream, soup, potato chips, carrot and bread), yielding both hedonic ratings (1–3) and rank order scores (1–8). Univariate and multivariable linear and logistic regression analyses were performed, using tasters as the reference group. Non‐tasters had a slightly higher preference for carrots (β: −0.07; 95% CI: −0.13, −0.02 and β: −0.15; 95% CI: −0.27, −0.02 for hedonic ratings and rank order scores, respectively) and bread (hedonic ratings; β: −0.06; 95% CI: −0.11, −0.01) compared with tasters. No differences were found in children's preference for sweet, fat or salty food items. Furthermore, there were no associations of PROP taster status with the consumption of high‐calorie snacks ≥ 2 times/day (aOR: 1.06; 95% CI: 0.91,1.24) or sweet beverages ≥ 3 glasses/day (aOR: 1.06; 95% CI: 0.92,1.23). Other factors relating to the family food environment may be more important for young children's food preferences and consumption of high‐calorie snacks and sweet beverages than their innate taste sensitivity.